Patterns at Multi-Spatial Scales on Tropical Island Stream Insect Assemblages (Gorgona Island Natural National Park, Colombia, Tropical Eastern Pacific) - Longo, Magnolia (2014)
Tropical Eastern Pacific island streams (TEPis) differ from other neotropical streams in their rainy climate, mixed sedimentary-volcanic geology and faunal composition. Yet, their relationships between environmental characteristics and stream biota remain unexplored. We analyzed the environmental subject at three spatial scales using a fully nested sampling design (6 streams, 2 reaches within each stream, 2 habitats within each reach, and 4 replicates per habitat) on Gorgona Island (Colombia). Sampling was carried out in two months with contrasting rainfall during early 2009. We studied the spatial variation of assemblage composition and density along with 27 independent variables within two contrasting rainfall conditions. Five stream-scale variables, two reach-scale variables, and five habitat-scale variables were selected using a Canonical Correspondence Analysis (CCA). A partial CCA showed that the total variance explained was 13.98%, while stream- and habitat-scale variables explained the highest proportion of the variance (5.74 and 5.01%, respectively). Dissolved oxygen (as affected by rainfall), high-density use zone (a management category), and sedimentary geology were the best descriptors of insect assemblages. The two latter descriptors affected fine-scale variables such as total benthic organic matter and gravel substratum, respectively. A Nested ANOVA showed significant differences in total density and richness among streams and habitats, and significant differences between the two sampling months regardless of the spatial scale. The evenness showed a significant stream- and habitat-dependent temporal variability. These results suggested that rainfall regime in Gorgona Island might be a driver of insect assemblage dynamics mediated by water chemistry and substratum properties. Spatial assemblage variability here is greater within habitats (among samples), and a minor fraction occurs at habitat- and stream-scales, while no longitudinal pattern was observed probably due to the short courses. Temporal variability should be further studied relative to rainfall and discharge regimes. Rev. Biol. Trop. 62 (Suppl. 1): 65-83. Epub 2014 February 01.